2018
DOI: 10.1159/000491468
|View full text |Cite
|
Sign up to set email alerts
|

Circ-ANAPC7 is Upregulated in Acute Myeloid Leukemia and Appears to Target the MiR-181 Family

Abstract: Background/Aims: Circular RNAs (circRNAs) are a family of novel non-coding RNAs associated with various diseases, especially cancer. Recent studies have demonstrated that circRNAs participate in pathogenesis mainly by acting as microRNA (miRNA) sponges. The expression profile of circRNAs in acute myeloid leukemia (AML) has rarely been reported. Methods: Profiles of circRNAs were analyzed using an Arraystar human circRNA microarray with 5 bone marrow samples from patients with newly diagnosed AML and 5 from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 28 publications
0
67
0
1
Order By: Relevance
“…A circRNA HIPK2, for example, sponged miR-124-3p to regulate the differentiation of all-trans retinoic acid (ATRA)-induced NB4 cells [155]. Chen et al [151] reported that circANAPC7 was significantly upregulated in AML and used an Arraystar human circRNAs microarray and bioinformatics analysis to predict when ANAPC7 might bind miR-181 family to participate in AML pathogenesis. An oncogenic activity of circRNA was also shown by DLEU2, which was highly expressed in AML, that inhibited miR-496 expression to promote cell proliferation and inhibit cell apoptosis [157].…”
Section: Prognostic Value Of Lncrnas In Acute Myeloid Leukemiamentioning
confidence: 99%
“…A circRNA HIPK2, for example, sponged miR-124-3p to regulate the differentiation of all-trans retinoic acid (ATRA)-induced NB4 cells [155]. Chen et al [151] reported that circANAPC7 was significantly upregulated in AML and used an Arraystar human circRNAs microarray and bioinformatics analysis to predict when ANAPC7 might bind miR-181 family to participate in AML pathogenesis. An oncogenic activity of circRNA was also shown by DLEU2, which was highly expressed in AML, that inhibited miR-496 expression to promote cell proliferation and inhibit cell apoptosis [157].…”
Section: Prognostic Value Of Lncrnas In Acute Myeloid Leukemiamentioning
confidence: 99%
“…For example, circRNA8924 is reported to promote proliferation and metastasis of CC cells through regulating CBX8 expression (J. Liu, Wang, Long, Liu, & Li, ). Also, circ‐ANAPC7 upregulation in acute myeloid leukemia promotes tumor progression through the miR‐181 family (H. Chen et al, ). In addition, circRNA circ‐BANP facilitates lung cancer development by the miR‐503/LARP1 pathway (Han et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…228 Similarly, the following circRNAs also function as a miRNA sponge in acute myeloid leukemia, such as circ_0009910 sponging miR-20a-5p, circ_100290 sponging to miR-203 and circ-ANAPC7 sponging to miR-181. [229][230][231] Furthermore, recent studies observed that circ-Foxo3 could compete with Foxo3 for binding to some miRNAs and then regulated the expression of Foxo3. 232 Circ-Foxo3 and Foxo3 were frequently decreased in AML and positively associated with each other.…”
Section: Myeloid Leukemiamentioning
confidence: 99%